A qualitative analysis of the factors that protect athletes against doping in sport. (January 2015) - Erickson, Kelsey; McKenna, Jim; Backhouse, Susan H.
Abstract: Objective: To explore the protective factors against performance enhancing drug (PED) use in sport. Design: Ten competitive athletes ( M = 5, F = 5) representing five different sports (field hockey, boxing, football, triathlon, rugby) were recruited through convenience sampling to undertake a semi-structured interview to enable a qualitative analysis of athletes' lifelong athletic careers. Method: Verbatim transcripts were analysed using an established three-stage coding process to identify the common themes within the narratives. Results: Personal and situational protective factors were identified in the accounts. Personal factors included: (i) a strong moral stance against cheating; (ii) an identity beyond sport; (iii) self-control; and (iv) resilience to social group pressures. Situational factors included secure attachments to people at all stages of the athlete's life. This facilitated both the promotion of moral decision making and assisted in the development of anti-doping attitudes. When situational factors – such as a pro-doping climate – arose, key attachments in the athletes' lives interplayed with personal factors to reduce the risk of doping. Conclusions: These findings offer insights into factors that protect competitive athletes against using PEDs in sport and further our understanding of the complex interaction between risk and protective factors at individual, psychosocial and societal levels among competitive athletes. As a complex behaviour, doping in sport cannot be prevented by solely focussing on the individual athlete; contextual factors beyond the athlete's control also impact on this behaviour. Thus, a paradigm shift is warranted to move beyond an athlete-centred approach to anti-doping. Highlights: We explore protective factors against doping in sport. Personal protective factors include self-regulation, strong moral stance and resilience. Family, school and community attachments are situational sources of protection. The relationship between risk and protective factors is complex and multifaceted. Education programs need to in-build factors beyond the individual and their choices.